Implementasi Metode AHP Dan Promethee Untuk Pemilihan Supplier - Chamid, Ahmad Abdul; Surarso, Bayu; Farikhin, Farikhin (Universitas Diponegoro, 2015)
Selection of suppliers is one of the most important things to meet the needs of the company consistently and at an acceptable cost, decision support system used to select suppliers by identifying suppliers with the highest potential. The object of this study is the drug suppliers. In this study we use four criterias to select suppliers of drugs: drug completeness, price, time delivery, payment or loan term. AHP method is used to calculate the weight of each criterion based on the pharmacist assessment. The weight criterias of the AHP process result is used for the calculation of the alternatives rank. PROMETHEE method used to alternatives calculation analysis that produce alternatives rankings.